Arthritic and non-arthritic synovial fluids modulate IL10 and IL1RA gene expression in differentially activated primary human monocytes. Issue 11 (November 2015) - Lopa, S.; Leijs, M.J.C.; Moretti, M.; Lubberts, E.; van Osch, G.J.V.M.; Bastiaansen-Jenniskens, Y.M.
Summary: Objective: Synovitis with an increased presence of macrophages is observed in osteoarthritis (OA) and rheumatoid arthritis (RA). Given the important role of macrophages in arthritis, we investigated the influence of OA and RA synovial fluid (SF) on primary human monocytes (Mo), their lineage precursors. Method: Adherent monocytes without any stimulation (Mo(−)) or stimulated with IFN-γ and TNF-α (Mo(IFN-γ/TNF-α)) or IL-4 (Mo(IL-4)) were exposed to SF from 6 donors without any known joint disease (SF-Ctrl), 10 OA donors (SF-OA), and 10 RA donors (SF-RA). The transcriptional expression of IL6, IL1B, TNFA, IL10, CCL18, CD206, and IL1RA was analyzed. Results: Mo(−) exposed to SF-RA had a lower expression of IL10 and a higher expression of IL1RA than when exposed to SF-Ctrl. Mo(IL-4) exposed to SF-RA had a lower expression of IL10 and CCL18 than when exposed to SF-Ctrl and Mo(IFN-γ/TNF-α) were not affected by SF-RA. Mo exposed to SF-OA also expressed less IL10, but only upon stimulation with IL-4, and expressed more IL1RA than when exposed to SF-Ctrl in any condition. Conclusion: A lower expression of IL10 may be regarded as a response to less inflammatory conditions since IL10 expression is higher in response to IFN-γ/TNF-α stimulation, probably as a feedback mechanism. Therefore, the lower expression of IL10 and the higher expression of IL1RA in Mo exposed to arthritic than to non-arthritic SF suggest that arthritic SF is mainly reducing the inflammatory responses in Mo. This may mimic the response of monocytes/macrophages recruited to the joint, where feedback mechanisms counteract pro-inflammatory processes.